Vanadium-doped hierarchical Cu2S nanowall arrays assembled by nanowires on copper foam as an efficient electrocatalyst for hydrogen evolution reaction. (15th April 2021) - Yang, Dan; Cao, Liyun; Huang, Jianfeng; Liu, Qianqian; Li, Guodong; He, Danyang; Wang, Jun; Feng, Liangliang
Abstract: A novel hierarchical vanadium-doped Cu2 S nanowall arrays assembled by nanowires (V-Cu2 S-Nanowires NW) on copper foam is synthesized by a facile one-step solvothermal method. Interestingly, the nanoparticles furtherly constitute the smallest unit of nanowires. Owing to the unique hierarchical structure with offering plentiful electronics/ions transport pathways and fully exposing catalytic active sites as well as optimizing hydrogen adsorption free energy due to vanadium doped effect, the V-Cu2 S-Nanowires NW demonstrates enhanced electrocatalytic activity towards hydrogen evolution reaction (HER) with a low loverpotential of 188 mV to drive 10 mA cm −2 and good durability for at least 20 h. This work provides an effective strategy for rational design of nanostructured Cu-based materials and enhanced energy-efficient hydrogen production. Graphical abstract: The in-situ growth of hierarchical vanadium-doped Cu2 S nanowall arrays assembled by nanowires (V-Cu2 S-Nanowires NW) on copper foam was reported for electrocatalytic hydrogen evolution reaction (HER). Image, graphical abstract